Postural and cortical responses following visual occlusion in standing and sitting tasks - Goh, K.; Morris, Susan; Lee, W.; Ring, A.; Tan, Tele (Springer-Verlag, 2017)
© 2017 Springer-Verlag Berlin HeidelbergPerturbation-evoked responses (PERs) to a physical perturbation of postural stability have been detected using electroencephalography (EEG). Components of these responses are hypothesized to demonstrate the detection (P1) and evaluation (N1) of postural instability. Despite the important contribution of the visual system to postural control, PERs to a visual perturbation of posture have yet to be reported. Ten healthy young adults were exposed to unpredictable visual occlusion mediated through liquid crystal glasses under two conditions of postural demand: quiet standing and quiet sitting. The participants’ PERs and postural responses were recorded and differences between conditions assessed using Wilcoxon signed-rank tests. In response to unpredictable visual occlusion, both P1 and N1 components of the PER were observed in both postural conditions. The amplitude of the P1 response remained consistent between postural conditions ((Formula presented.), (Formula presented.)), whereas N1 amplitude and postural responses were significantly smaller in the sitting condition ((Formula presented.), (Formula presented.)). This is the first study to demonstrate cortical responses to visual perturbation of posture. The responses to postural perturbation by sudden visual occlusion are similar in nature to that seen in relation to a physical perturbation. In addition, the amplitude of the N1 response is not only consistent with the relative magnitude of the perturbation, but also the underlying postural set, with a larger N1 seen in standing relative to sitting. The study informs the relative importance of vision to postural stability, postural set and provides a protocol to objectively assess sensory-based postural disorders.